Smallholder pork: Contributions to food and nutrition security - Roesel, Kristina (Elsevier, 2019)
The article summarizes the current global distribution and burden of malnutrition and then outlines how animal sourced foods such as milk, meat, eggs and fish can contribute to a balanced human diet, especially in low- and middle income countries where meals are largely starch-based and lacking diversity. The last part outlines the nutritional composition of pork, and shows how smallholder pig keeping is increasingly popular in these countries as a source of food and income.